2017
DOI: 10.4067/s0250-71612017000300047
|View full text |Cite
|
Sign up to set email alerts
|

A transformação da zona ribeirinha oriental de Lisboa: um caso de gentrificação por nova construção

Abstract: resumo | O Parque das Nações em Lisboa, área ribeirinha residencial, comercial, de serviços e de usufruto lúdico, resulta de uma intervenção urbana de iniciativa pública associada à realização Expo'98. A intervenção caracterizou-se pela total demolição do edificado e pela substituição de populações com poucos recursos socioeconómicos por populações com maiores recursos. São objetivos deste artigo: (i) retratar a zona na época anterior à demolição como espaço de vivência e descrever o processo de expulsão das p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…The trend that seems more solid at present is the (limited) migration towards private long-term rental and a relatively significant migration to medium-term rental. This latter response, as well as offering the hosts more flexibility by allowing a mixed system that could be exploited in association with STR, may become more popular in the wake of changes resulting from Covid (essentially, but not exclusively in cities): the increase of life-style migrations (Hayes, 2018) digital nomads, investors, retired, highly qualified staff, etc.in countries, such as Portugal, where geo-arbitrage -"taking advantage of international price differences in costs of living for personal or business purposes" (Penney and Dramowicz, 2016:1)is promising (Pereira, 2022). Additionally, and especially in cities, the majority of STRswhether due to their location (in historic centres with specific urban morphologies, equipment and experiences) or due to their housing typologies (minimalist housing in terms of size, comfort and facilities)are much more suited to 'transitory experiences' than they are for long-term appropriation as experienced in traditional rentals.…”
Section: Discussionmentioning
confidence: 99%
“…The trend that seems more solid at present is the (limited) migration towards private long-term rental and a relatively significant migration to medium-term rental. This latter response, as well as offering the hosts more flexibility by allowing a mixed system that could be exploited in association with STR, may become more popular in the wake of changes resulting from Covid (essentially, but not exclusively in cities): the increase of life-style migrations (Hayes, 2018) digital nomads, investors, retired, highly qualified staff, etc.in countries, such as Portugal, where geo-arbitrage -"taking advantage of international price differences in costs of living for personal or business purposes" (Penney and Dramowicz, 2016:1)is promising (Pereira, 2022). Additionally, and especially in cities, the majority of STRswhether due to their location (in historic centres with specific urban morphologies, equipment and experiences) or due to their housing typologies (minimalist housing in terms of size, comfort and facilities)are much more suited to 'transitory experiences' than they are for long-term appropriation as experienced in traditional rentals.…”
Section: Discussionmentioning
confidence: 99%
“…Com isso, a atuação do bacharel em Gerontologia tem ganhado novos espaços e papéis e se destacado por ter uma formação multidisciplinar, visão holística de análise e humanização na forma de tratar e planejar suas estratégias, permitindo uma maior resiliência e mobilidade no mercado (Lima, 2009). Atualmente, tem se fortalecido em setores como Gestão de Unidades de Saúde, Gestão de Casos, Equipe e de Projetos, Área de Planejamento, Operacional e Administração em Saúde (Martín, 2006;Pavarini et al, 2005;Pereira, 2008).…”
Section: O Gerontólogo Como Facilitador E Articulador Da Interdiscipl...unclassified
“…More recently this spatiality was broadened. New studies identified forms of gentrification supported not on the historical characteristics of central neighbourhoods any longer, but on new constructions (Davidson & Lees, 2010;López-Morales, Gasic Klett & Meza Corvalán, 2012), some of them outside the central areas (Pereira, 2017). In these cases, the construction of new buildings can occur in spaces that previously residential or possessing other former uses, such as industrial or commercial.…”
mentioning
confidence: 99%